Removal of Ammonia Gas via Conducting Polymer-Assisted Titania Under Visible-Light or UV Exposure - Yang, Sung-Bong; Jo, Wan-Kuen; Cho, Sung-Back; Yu, Mee-Seon (Asian Journal of Chemistry, 2015)
Conducting polyaniline (PANI)-assisted titania (PANI-TiO2) composite was synthesized using a facile hydrothermal-chemisorption method. Its surface characteristics were determined using UV-visible, scanning electron microscopy and Fourier transform infrared techniques. In addition, its application for photocatalytic removal of airborne ammonia under visible- or UV-light exposure was evaluated. Scanning electron microscopy images confirmed that both the PANI-TiO2 composite and unmodified TiO2 were composed of polydispersed microsphere-shaped particulates, while P25 TiO2 displayed much smaller particle shapes. Fourier transform infrared results for the PANI-TiO2 composite indicated that polyaniline could be embedded into TiO2. The PANI-TiO2 composite and two reference photocatalysts (unmodified TiO2 and P25 TiO2) had a similar variation in the adsorption efficiencies of ammonia over time. However, the photocatalytic removal efficiencies for ammonia obtained using the PANI-TiO2 composite under visible-light exposure were higher than the results obtained from the two reference photocatalysts. The photocatalytic removal efficiencies for ammonia with all three photocatalysts were about 100 % under UV exposure conditions, which did not allow for a comparison of the photocatalytic removal efficiencies of the three photocatalysts. The average photocatalytic removal efficiency over the PANI-TiO2 composite decreased from 83 to 39 %, as the reaction time increased from 2.5 to 15.2 s. Overall, PANI-TiO2 composites can be utilized to remove ammonia gas under visible-light as well as UV irradiation.